Determination of the yearly distribution of the incidence of Allergic Bronchopulmonary Aspergillosis (ABPA) in patients registered in the cystic fibrosis patient registry system of Turkey and identification of risk factors for its development - Demir H. I.; Yalcin E.; Buyuksahin H. N.; Savas S.; ŞEN V.; ŞEN H. S.; Baskan A. K.; Kilinc A. A.; YAZAN H.; ÇOLLAK A.; et al. (My University, 2026)
Background Allergic bronchopulmonary aspergillosis (ABPA), is a hypersensitivity reaction in the lung against the antigens of Aspergillus fumigatus. The aim of this study is to determine the incidence of ABPA, and to determine the risk factors leading to the development of ABPA.Methods The study was designed as a retrospective cohort study. Using the CF Registry System of Turkey data, the incidence of ABPA was determined and the clinical and demographic characteristics of 44 patients newly diagnosed with ABPA in 2022 and 132 patients with similar mutation weight and age range without ABPA diagnosis in that year were examined and compared. Also risk factors affecting the development of ABPA were determined.Results Low pulmonary function test values, having had at least one pulmonary exacerbation in that year, receiving intravenous antibiotic treatment, using inhaled antibiotics, having high number of pulmonary exacerbations, having Pseudomonas aeruginosa colonization, having low body mass index (BMI), having cystic fibrosis related diabetes mellitus were found to be among the risk factors for the development of ABPA.Conclusions Early recognition and treatment of ABPA is essential to prevent further damage to the lungs. Patients with frequent pulmonary exacerbations, low BMI and low pulmonary function test values, chronic colonization should definitely be considered for ABPA.
Keywords: Tıp; Dahili Tıp Bilimleri; Aile Hekimliği; Sosyal ve Beşeri Bilimler; Sosyoloji; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Internal Medicine Sciences; Family Medicine; Social Sciences and Humanities; Sociology; Health Sciences; Fundamental Medical Sciences; Sağlık Bakım Bilimleri ve Hizmetleri; Klinik Tıp; Klinik Tıp (Med); Kamu Çevre ve İş Sağlığı; Sosyal Bilimler Genel; Sosyal Bilimler (Soc); Tıp Genel & Dahili; Health Care Sciences & Services; Clinical Medicine; Clinical Medicine (Med); Public Environmental & Occupational Health; Social Sciences General; Social Sciences (Soc); Medicine General & Internal; İş Sağlığı ve Terapisi; Tıbbi Terminoloji; Tıbbi Sekreterlik ve Transkripsiyon; Sağlık Bilgi Yönetimi; Sağlık Meslekleri (çeşitli); Genel Sağlık Meslekleri; Güvenlik Araştırması; Sağlık (sosyal bilimler); Genel Sosyal Bilimler; Gözden Geçirme ve Sınav Hazırlığı; Patofizyoloji; Liderlik ve Yönetim; Temel Bilgi ve Beceriler; Toplum Sağlığı ve Evde Bakım; Bakım Planlaması; Değerlendirme ve Teşhis; Halk, Çevre ve İş Sağlığı; Dahiliye; Sağlık Politikaları; Aile Sağlığı; Epidemiyoloji; Tıp (çeşitli); Genel Tıp; Sosyal Bilimler ve Beşeri Bilimler; Occupational Therapy; Medical Terminology; Medical Assisting and Transcription; Health Information Management; Health Professions (miscellaneous); General Health Professions; Safety Research; Health (social science); General Social Sciences; Review and Exam Preparation; Pathophysiology; Leadership and Management; Fundamentals and Skills; Community and Home Care; Care Planning; Assessment and Diagnosis; Public Health, Environmental and Occupational Health; Internal Medicine; Health Policy; Family Practice; Epidemiology; Medicine (miscellaneous); General Medicine; Social Sciences & Humanities